HOTAIR is upregulated in acute myeloid leukemia and that indicates a poor prognosis - Hao, Shanfeng (Int J Clin Exp Pathol, 2015)
Hox transcript antisense intergenic RNA (HOTAIR) is a long non-coding RNA, its overexpression has been documented in various human solid tumor and it can be considered as a potential cancer biomarker. However, little is known about the role of HOTAIR in acute myeloid leukemia (AML). In this study, We evaluated HOTAIR expression in bone marrow of de novo AML patients, AML-CR patients and normal controls by real-time quantitative reverse transcription-PCR (qRT-PCR), then we inhibited hotair expression of two cell lines by siRNA and evaluated their proliferation by CCK, finally we analyzed its relationship with the clinicopathological parameters of AML. We found that HOTAIR is significantly upregulated in de novo AML patients compared with those of AML-CR patients and normal controls; the reduction of HOTAIR by small interfering RNA (siRNA) repressed the proliferation of HL-60 and K562; the higher expression level of HOTAIR in AML patients was significantly correlated with NCCN high risk group. In conclusion, our study indicated that hotair is highly expressed in AML patients, and hotair expression significantly correlates with clinicopathological prognostic stratification in AML.